Evaluation of new castor pistillate lines for agro-morphological characters and sex expression in different seasons: Evaluation of new castor pistillate lines for agro-morphological characters and sex expression in different seasons - C LAVANYA; T MANJUNATHA; S SENTHILVEL (Journal of Oilseeds Research, 2020)
A total of 41 new castor pistillate lines along with three checks were evaluated in two sets during rabi and late kharif under irrigated and rainfed conditions to study the variability for nine agro-morphological traits and sex expression. Based on better performance than the checks, both for seed yield and pistillate expression, ten pistillate lines were identified for further studies on heterosis and combining ability